CRC handbook of phase equilibria and thermodynamic data of aqueous polymer solutions - Wohlfarth, C. (Taylor & Francis, 2012)
"This comprehensive source provides a complete collection of thermodynamic data of polymer solutions. It helps readers to quickly retrieve all of the relevant information that they need from the literature and also assists researchers in planning new measurements where data are missing. The author, who clearly explains how measurements were conducted and methodically explains his nomenclature, presents data essential for the product and use of polymers as well as for understanding the physical behavior and intermolecular interactions in polymer solution. This text is a valuable resource for the modern chemistry field, where pharmacy and biotechnology water soluble polymers play an important role"--